Effectiveness of the manchester triage system in the emergency department: A literature review - Andika I Putu Juni; Safaruddin; Christina Tri Yahya; Baso Yusriani Saleh; Utami Seftiani (BIO Web of Conferences)
Congestion in emergency rooms is a worldwide problem that is frequently caused by rising patient volumes, which can lead to organizational challenges. The Manchester Triage System (MTS) and other triage systems seek to enhance patient flow management and forecast the severity of illnesses. This study assesses how well MTS categorizes patients in emergency rooms according on their risk. Using inclusion and exclusion criteria, a literature analysis was carried out, and papers were sourced from databases such as Science Direct (2020–2024), PubMed (2020–2024), and Google Scholar (2019–2024). Efficacy, Manchester Triage System, and Emergency Department were among the search phrases used. Full texts of articles released between 2019 and 2024 were obtained once their applicability was assessed. The results confirm that MTS is applicable to a range of patient populations, including adults, children, and those suffering from acute pulmonary embolism and coronary syndromes. In terms of forecasting ED visits and short-term mortality, the MTS proved to be reliable. Sub-triage and super-triage (misclassification of severity) problems persist despite its efficacy. The majority of research leads to the conclusion that MTS is a helpful tool for patient triage in emergency situations, improving patient outcomes and resource allocation.